Aspect–perfect and imperfect traditional qualities. Analysis and inconsistency - Vásquez González, Jorge Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Here, the Spanish grammatical aspect and its traditional qualities in perfect and imperfect verb forms are analyzed in order to expose a problem of conceptual inconsistency. Taking into account the Real Academia Española (RAE) normativity, there is a misperception in the aspectual distinction between the simple and compound tenses in Spanish, or in Latin, infectum and perfectum. After a proper understanding of the concept of participle , formed by the auxiliary to have , a different terminology is proposed to solve the problem: the terms continuous and discontinuous are proposed as new qualities of the grammatical aspect. Such a change would also suggest a new verbal accident: that of state . An explanatory methodology was implemented in this project, in order to specify the concept of aspect in the field of the Spanish language. To a lesser degree, a descriptive methodology was also used, by means of the presentation of specific, insightful examples to support the current concept of aspect .